2002
DOI: 10.1074/jbc.m207758200
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Organization of Cationic Lipid-DNA Complexes

Abstract: The interaction of cationic liposomes with supercoiled plasmid DNA results in a major rearrangement of each component to form compact multilamellar structures comprised of alternating layers of two-dimensional arrays of DNA sandwiched between lipid bilayers. Fluorescence resonance energy transfer was used to estimate the distance of closest approach of DNA to the lipid bilayers in these complexes. The effect of several compositional variables on this distance, including the ratio of cationic lipid to DNA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…The results are in agreement with spectroscopic and enzymatic data, reported recently, in which the detection of partial denaturation in plasmidic DNA lipoplexes by increased hyperchromicity and nuclease susceptibility [20], and other methodologies was described [6][7][8][9][10]17]. They strongly suggest that the ODN composition can affect both the electrostatic and aggregation processes that occur during an ODN cationic liposome complexation event, and consequently can influence the efficiency of lipoplex transfection capacity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results are in agreement with spectroscopic and enzymatic data, reported recently, in which the detection of partial denaturation in plasmidic DNA lipoplexes by increased hyperchromicity and nuclease susceptibility [20], and other methodologies was described [6][7][8][9][10]17]. They strongly suggest that the ODN composition can affect both the electrostatic and aggregation processes that occur during an ODN cationic liposome complexation event, and consequently can influence the efficiency of lipoplex transfection capacity.…”
Section: Discussionsupporting
confidence: 80%
“…It was reported that DOTAP cationic liposomes form more stable lipoplexes with relaxed DNA structures when plasmidic DNA has been used [20] and some similar features of the lipoplex generation driving force may be connected with the present work.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…DLS studies have identified CL-DNA particles in the size range 50-300 nm and confirmed their intrinsic heterogeneity (23)(24)(25). Their  potentials range from the highly negative (an excess of DNA) to the highly positive (an excess of CL).…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 90%
“…In the case of lipoplexes, it has been possible to label the DNA by either intercalation of a dye between the bases or binding of a dye to the minor groove (donors). Then, a different dye can be placed within the bilayer of the CLs (acceptors); this makes it possible to estimate the mean distance between various sites within the complexes (23,42). Although they have only been explored to a limited extent, versions of this approach may turn out to be quite useful.…”
Section: Circular Dichroism (Cd)mentioning
confidence: 99%